1976
DOI: 10.1126/science.1082167
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transplant Immunity: Effect of Donor Leukocytes on Thyroid Allograft Rejection

Abstract: The survival of thyroid allografts in mice was prolonged by either holding the grafts in vitro culture for 20 to 27 days or by cobalt-60 irradiation of the donor 2 days before transplantation with or without the intravenous injection of colloidal carbon just before removing the thyroid from the donor. In both cases the rejection process was restored by an intravenous injection of recipients with living peritoneal exudate cells (50 to 80 percent macrophages) syngeneic to the thyroid donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(81 citation statements)
references
References 12 publications
2
78
1
Order By: Relevance
“…For transplanted tissues such as skin, donor DC migrate from the graft via the dermal lymphatic vessels into draining lymph nodes (12). Improvement in graft survival following depletion of leukocytes from thyroid, pancreatic islet, skin, or kidney allografts supports the concept that trafficking and maturation of donor DC in recipient lymphoid organs lead to the activation of naive, alloreactive Th0 lymphocytes, and thus provides the primary stimulus for acute allograft rejection (18,43,44). By contrast, in the absence of immune suppression, liver allografts (that possess comparatively large numbers of passenger leukocytes) can induce donor-specific tolerance in fully MHC-mismatched mouse and certain rat strain combinations, and in a high proportion of outbred pigs (19,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 95%
“…For transplanted tissues such as skin, donor DC migrate from the graft via the dermal lymphatic vessels into draining lymph nodes (12). Improvement in graft survival following depletion of leukocytes from thyroid, pancreatic islet, skin, or kidney allografts supports the concept that trafficking and maturation of donor DC in recipient lymphoid organs lead to the activation of naive, alloreactive Th0 lymphocytes, and thus provides the primary stimulus for acute allograft rejection (18,43,44). By contrast, in the absence of immune suppression, liver allografts (that possess comparatively large numbers of passenger leukocytes) can induce donor-specific tolerance in fully MHC-mismatched mouse and certain rat strain combinations, and in a high proportion of outbred pigs (19,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 95%
“…30,31 The evidence Implicating these antigen-presenting cells in primary T-cell alloimmunity 22,30,32 has prompted efforts to eliminate them before transplantation. 33,34 .…”
mentioning
confidence: 99%
“…M ore than 20 years ago, Lafferty and colleagues and, subsequently, Lechler and Batchelor demonstrated that the main immunogenic stimulus leading to graft rejection was provided by the migrant population of allogeneic "passenger" dendritic cells (DC) 3 present in the allografted tissue (1)(2)(3)(4). If the graft was depleted of these cells, rejection was less strong or was absent, and graft survival was extended.…”
mentioning
confidence: 99%